Analysis of long-term outcomes after minimally invasive spleen-preserving distal pancreatectomy under the 'Kimura-first' strategy - Xin Luo; Xianchao Lin; Ronggui Lin; Yuanyuan Yang; Congfei Wang; Haizong Fang; Heguang Huang; Fengchun Lu (Journal of Minimal Access Surgery, 2024)
Introduction: Spleen-preserving distal pancreatectomy (SPDP) can be carried out by the Kimura technique (KT) or Warshaw technique (WT). This study aimed to evaluate the long-term post-operative outcomes of the two minimally invasive SPDP methods under the 'Kimura-first' strategy with a particular focus on the haemodynamic changes in the splenogastric circulation. Patients and Methods: The electronic medical records and follow-up data of patients who underwent minimally invasive SPDP in our centre from March 2016 to July 2022 were reviewed. The haemodynamic changes in splenogastric circulation were monitored by post-operative computed tomography (CT) images, and the risks they caused were assessed by long-term follow-up. Results: A total of 112 patients (KT = 93 and WT = 19) were included in the study. The tumour size in the WT group was significantly larger than that in the KT group (P = 0.02). We also found less blood loss for patients who underwent KT (P = 0.02). The occurrence of gastric varices was significantly higher in the WT group (P = 0.022). There was no gastrointestinal bleeding in either group. There were two cases of splenic infarction in the WT group (11.1%), and the incidence was higher than that in the KT group (P = 0.026). The infarct area gradually decreased during periodic CT examinations and disappeared completely at the last review. The two groups of patients had similar results across the 15 items in three areas of the quality of life questionnaire. Conclusions: The 'Kimura-first' strategy, in which the WT is used as an alternative to the KT when the splenic vessels cannot be safely preserved, is feasible, and safe for minimally invasive SPDP.